In Situ Synthesis of Ultrathin Graphene‐Like Nanosheets as a Highly Effective Oxygen Catalyst for Zinc−Air Batteries. Issue 15 (13th August 2019) - Wu, Chao; Song, Li; Li, Linghui; Xia, Wei; Jiang, Cheng; Gao, Bin; Du, Yanqiu; Wang, Tao; He, Jianping
Abstract: Two‐dimensional materials have large specific area, high electron transfer capability and abundant exposed active sites, which are beneficial to improve their catalytic properties. Here, we used a simple salt‐template method to construct ultrathin graphene‐like Fe/N−C nanosheets (named as Fe/GNS‐1.5). During the synthesis process, NaCl crystallite serves as a rigid template of two‐dimensional mesoscopic structure. Iron nitrate acts as a gas‐foaming agent, which plays pivotal part in the morphology and structure of catalysts. The obtained Fe/GNS‐1.5 nanosheets with a thickness of 3 nm have a large specific surface area (705 m 2  g −1 ). Benefiting from the structure advantages, Fe/GNS‐1.5 exhibits a great bifunctional catalytic performance. The Fe/GNS‐1.5 catalyst is employed as air cathode of zinc−air battery to examine its practical application, which presents excellent power density (156 mW cm −2 ) and favorable cyclic stability for more than 600 cycles. Abstract : Just add some salt : Two‐dimensional ultrathin graphene‐like bifunctional nanosheets are synthesized by a salt template method. The iron/nitrogen doped ultrathin graphene‐like nanosheets display excellent bifunctional catalytic performance. Fe/GNS‐1.5 based zinc−air battery shows outstanding battery performance.